Nursing care related to infection in the indwelling bladder cateter (Research, Society and Development, 2023)
Introduction: the indwelling urinary catheter (SVD) is a health instrument that is used for water balance and to relieve patients with enuresis, urinary catheter infection is a disease present in patients with SVD, which has related risk factors such as contamination by microorganism or the female sex factor. Objective: to analyze the importance of nursing care in preventing urinary tract infections caused by bladder catheterization. Methods: integrative literature review, carried out with articles available in the BDENF, ScieLO, MEDLINE and VHL databases. Results: articles were found that demonstrate the SVD procedure, risk factors such as infection and the attributions of the nursing team to reduce urinary catheter infection. Conclusion: it was identified the main secondary complications and some procedures that can influence the prevention of urinary tract infections related to the catheter.